Mass flowering of the tropical tree Shorea beccariana was preceded by expression changes in flowering and drought‐responsive genes. Issue 18 (8th May 2013) - Kobayashi, Masaki J.; Takeuchi, Yayoi; Kenta, Tanaka; Kume, Tomonori; Diway, Bibian; Shimizu, Kentaro K.
Abstract Community‐level mass flowering, known as general flowering, which occurs in South‐East Asia at supra‐annual irregular intervals, is considered a particularly spectacular phenomenon in tropical ecology. Recent studies have proposed several proximate factors inducing general flowering, such as drought and falls in minimum temperature. However, limited empirical data on the developmental and physiological processes have been available to test the significance of such factors. To overcome this limitation and test the hypotheses that general flowering is triggered by the proposed factors, we conducted an 'ecological transcriptome' study of a mass flowering species, Shorea beccariana, comparing meteorological data with genome‐wide expression patterns obtained using next‐generation sequencing. Among the 98 flowering‐related genes identified, the homologs of a floral pathway integrator, SbFT, and a floral repressor, SbSVP, showed dramatic transcriptional changes before flowering, and their flowering functions were confirmed using transgenic Arabidopsis thaliana. Expression in drought‐responsive and sucrose‐induced genes also changed before flowering. All these expression changes occurred when the flowering‐inducing level of drought was reached, as estimated using data from the preceding 10 years. These genome‐wide expression data support the hypothesis that drought is a trigger for general flowering.